Policy Evaluation of the Smart Indonesia Program (PIP) in Handling School Dropouts in Pandeglang Regency (Study in Pasirpanjang Village, Picung District) - Nurdin, Ali; Maharani, Vifi Intan (Lenggogeni Data Publishing, 2025)
This study aims to evaluate the policy implementation of the Indonesia Smart Program (Program Indonesia Pintar/PIP) in addressing school dropouts in Pandeglang Regency, focusing on Pasirpanjang Village, Picung District. The PIP is a government initiative that provides financial assistance to students from low-income families to help them continue their education. However, its implementation still faces issues such as inaccurate targeting and delays in fund distribution. The research employed a descriptive qualitative approach, with data collected through interviews and documentation. Policy evaluation was analyzed using William Dunn’s indicators of effectiveness, efficiency, adequacy, and responsiveness. The results indicate that the implementation of PIP in Pasirpanjang Village generally runs as expected and meets most policy evaluation indicators, yet it remains imperfect due to issues in targeting accuracy and coordination. The main inhibiting factors include delayed fund disbursement and lack of public understanding regarding program mechanisms, while supporting factors include the commitment of local government and the active role of schools in identifying eligible students.